PENGUKURAN KINERJA PELAYANAN PADA PUSAT KESEHATAN MASYARAKAT GAYUNGAN SURABAYA - Prasetia, Muhammad Yuga; Ngumar, Sutjipto (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to find out how the performance of the employees at Puskesmas Gayungan Surabaya in providing medical service which is located on jalan Gayung Sari Barat No. 124 Surabaya. The qualitative descriptive has been applied as data analysis method. The data has been retrieved from the preliminary survey technique and field study by performing documentation, interview, and questionnaire. The result of the survey which has been conducted in Puskesmas Gayungan Surabaya about the measurement of the performance of the employees the overall result of index is 2.99 and the value of Community Satisfaction Index after it has been converted is 2.99 x 25 = 74.75 is the category of the criteria of service quality and service performance in the field of medical (Puskesmas Gayungan Surabaya) with the good result. It can be concluded from the above discussion that the importance of General Guideline of the Preparation of Community Satisfaction Index as the service performance measurement particularly the public sector organization should be implemented every year which is meant to find out the rate of the performance of service quality periodically.Keywords: employees performance measurement, service and community satisfaction index